Exoasota pursatensis Ko & Bae, new genus and species of the Spilomelinae (Lepidoptera: Pyraloidea: Crambidae) from Indochina - Ko, Jae-Ho; Bayarsaikhan, Ulziijargal; Park, Bo-Sun; Lee, Tak-Gi; Cha, Yeong-Bin; Jang, Chang-Moon; Lee, Jong Koo; Bae, Yang-Seop (Zootaxa, 2020)
Exoasota pursatensis Ko & Bae, gen. nov. & sp. nov. (Lepidoptera: Pyraloidea: Crambidae) is described from Indochina (Cambodia, Thailand, Vietnam, Myanmar). The new genus Exoasota is assigned to Spilomelinae on the basis of the morphological evidence, including the tympanal organs and genitalia. In addition, we provide comparisons with genera Epiparbattia Caradja (Crambidae, Pyraustinae) and Asota Hübner (Erebidae, Aganainae). Illustrations of adults, genitalia, and tympanal characters are provided.